THE EFFECT OF WORK STRESS AND WORK DISCIPLINE ON TURNOVER INTENTION OF PT ULTRAJAYA MILK INDUSTRY & TRADING COMPANY EMPLOYEES - Farrel Ahmad Fathari; Shinta Oktafien (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Turnover is a business issue, especially in manufacturing. The impact is higher staff turnover, stress from a hard task, a poor business image, and a bad work environment. PT Ultrajaya Milk Industry & Trading Company has high turnover owing to job offers, work discipline infractions, and other factors. Work stress and work discipline affect employee turnover intention at PT Ultrajaya Milk Industry & Trading Company. This study used 118 respondents and 91 production staff. Sampling is random. A questionnaire gathers data. All goods tested legitimate and dependable. IBM SPSS 23 is used for classical assumption and multiple linear regression data analysis. Work discipline has no positive or negligible effect on turnover intention, whereas fluctuating work stress has a huge and beneficial effect. Work stress and discipline significantly affect turnover intention, according to multiple linear regression.